Short-rotation bioenergy stands as an alternative to spruce plantations: implications for bird biodiversity - Lindbladh, Matts; Hedwall, Per-Ola; Wallin, Ida; Felton, Annika; Böhlenius, Henrik; Felton, Adam (Silva Fennica, 2014)
Global efforts to decrease dependence on fossil fuels have increased interest in bioenergy production. One source of bioenergy is fast growing deciduous tree species, such as hybrid aspen ( Ã HÃ¤met-Ahti). The majority of research on hybrid aspen which assesses biodiversity implications, has however primarily focused on agricultural lands as the reference condition. This has resulted in a substantial gap in our knowledge regarding the biodiversity implications of replacing production forest types with hybrid aspen, a form of reforestation taking place in northern Europe. In this study we address this knowledge gap by comparing the avian biodiversity of young hybrid aspen and spruce ( L.) plantations of similar age, the latter being the most prevalent forestry alternative in in southern Sweden. We found that hybrid aspen stands had higher bird species richness and abundance as well as a distinct community composition compared to the spruce stands. We suggest that the most likely driver was the greater structural and tree species complexity in the aspen stands, provided for by the fenced exclusion of ungulates from the regenerating hybrid aspen stands. Our results indicate that at least during early stages of regeneration, and in comparison to the dominating production forest type in the region, hybrid aspen stands can support relatively high levels of bird diversity, and a bird species composition more closely associated with broadleaf habitat types requiring restoration in this region.PopuluswettsteiniiPicea abies